EFFECT OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION THERAPY ON PAIN AND FUNCTIONAL DISABILITY LEVEL AMONG PATIENTS WITH ROTATOR CUFF DISEASE- A RANDOMIZED CONTROLLED TRIAL (International Journal of Physiotherapy, 2020)
Background: Shoulder pain is one of the leading causes of musculoskeletal pain and disability with rotator cuff disease was a common condition. The study aimed to assess the effect of TENS therapy on pain and functional disability level with rotator cuff disease patients.Methods: A parallel-group randomized controlled with 1:1 allocation, open-label, the trial is done at Orthopaedics and Physical Medicine and Rehabilitation Out Patient Departments, AIIMS, Rishikesh, Uttarakhand, India. After applying inclusion and exclusion criteria total of 76 patients (42 males,34 females) of rotator cuff disease were selected through total enumerative sampling, and block randomization with a block size of two is used to allocate treatments. The intervention was TENS therapy (high frequency (100Hz) with a pulse duration 120μsand low intensity (30- 40mA) for 20 minutes.) for consecutive five days plus standard treatment for the experimental group and standard treatment (Shoulder ROM, twice a day) as followed at AIIMS, Rishikesh to control group and Followed after completion of the treatment session. (after five days). SPADI scale is used for pain and functional disability level measurement.Results: A total of 70 patients (38 males and 32 females) were analyzed. The experimental and control group were homogenous in terms of total SPADI, disability and pain score (p>0.05). Median post-intervention total SPADI, disability and pain scores of the intervention group were significantly less as compared to the control group (p=0.000). No side- effects of treatment in any group.Conclusion: TENS therapy is an efficient therapy for patients experiencing rotator cuff diseaseTrial registration- CTRI/2018/09/015659